Diversity patterns of Oniscidea (Isopoda, Crustacea) associated with Brazilian caves - Pereira, Rafaela Bastos (2018)
Understanding the patterns of species distribution represents a fundamental aspect not only for Biogeographical studies providing indications of previous conditions that drove the lineages to where we observed them in the present, but also providing support to conservation actions. Although this is largely explored for several taxa worldwide, the subterranean fauna still lacks information on this issue. This thesis was conducted in order to elucidate the distribution patterns of Oniscidea associated with Brazilian caves, specifically testing if they present a latitudinal gradient of richness and range size. Moreover, areas of endemism (AE) were delimited based on the geographical interpolation of endemism, for which the index of taxonomic distinctness (∆*) was calculated. Posteriorly priority areas of conservation of cave isopods were indicated, consequently of the landscape with which they are associated and all the biodiversity that it contains. Neither richness nor range size are significantly related to the latitude, but rather to the number of caves present in the same latitudinal range. Any significant relationship was observed when troglobites were disregarded. Fourteen AEs were identified, among which the Speleological Province of Arcos-Pains-Doresópolis (SPAPD) and Southern Karst of Bahia stood out as the richest areas, while PETAR and Chapada Diamantina presented the highest values of ∆*. SPAPD was more intensively evaluated in order to compare the patterns of taxonomic, phylogenetic and functional diversity of epigean and hypogean assemblages of Oniscidea, especially testing the effects of troglobites over these patterns, besides verifying which component of β diversity predominates as assembly rule. When disregarding troglobites any significant difference was observed between the taxonomic, phylogenetic and functional diversity of epigean and hypogean habitats, although when they are considered the caves present higher taxonomic diversity. Furthermore, the overall functional diversity was higher in the hypogean habitat, but there were not significant differences between the functional β diversity of the two environments. Therefore, the troglobites are the great responsible by the taxonomic singularity of caves, which are richer in phylogenetically related and functionally redundant species. Such results reinforce the need to conduct analysis manipulating the presence of some species to test their effects over the observed patterns, as well as of using integrative approaches when evaluating the diversity patterns.